A bridgeless AC-DC step up regulator circuit for piezoelectric energy harvester - Issa, Adel; Shufat, Salem; Ahmed, Jamal; Abunouara, Jamal (Journal of Pure & Applied Sciences, 2023)
Various applications of the piezoelectric energy in the modern world require an efficient AC-DC low power converter. As the two stages converter with bridge rectifiers may not be used because the diodes would not be suitable for low volt ranging between 100 to 200mv, these are considered an efficient element in the low volt circuits because of their entire losses.  In this paper, a small and efficient AC-DC low power converter is presented. It directly converts low AC voltage to the required output DC voltage using one stage instead of bridge rectification. The proposed converter combines both boost and buck boost converters which are parallel constructed to condition the positive and negative half cycle of the input AC volt respectively. Two inductors and one capacitor are used for booth circuits in terms of reducing the size. The circuit is tested at 50 kHz switching frequency with two different duty cycles to rectify a 0.5 AC volt to about 3 DC volts with an estimated efficiency of 65%. The simulation result was 3.7 DC V from 0.5 ACV. The circuit analysis and the design guide line are explained. The circuit is designed and tested using Matlab (Simulink) software.